Advancements in Transmitters and Sensors for Biological Tissue Imaging in Magnetic Induction Tomography - Zulkarnay, Zakaria; Ruzairi, Abdul Rahim; Muhammad Saiful Badri, Mansor; Sazali, Yaacob; Nor Muzakkir, Nor Ayob; Siti Zarina, Mohd. Muji; Mohd Hafiz Fazalul, Rahiman; Syed Mustafa Kamal, Syed Aman (MDPI AG, 2013)
Link to publisher’s homepage at http://www.mdpi.com/